Teaching and Learning to Teach with Recursive Mediated Learning Experiences - Reuben L. Yarmus; James J. Vagliardo (European Teacher Education Network, 2014)
Data points continue to underscore an alarming crisis in U.S. public education especially for poor children, non- whites and English Language Learners as well as persistent, pervasive demographic dissonance between future teachers and learners. Given this crisis and dissonance, those charged with preparing the next generation of educators need to identify innovative ways to confront bias, assumptions, pseudo-concepts, "status quo" and complicity and to foster a sense of social justice and a spirit of relentlessness. Inspired by the work of Vygotsky and of Feuerstein and based upon their own action research, the authors propose recursive mediated learning experiences, detailing a number of activities that they are utilizing in courses on campus and during practice teaching to draw future teachers, university instructors and P-12 mentor teachers "under the hood" in engaging, collaborative, process-oriented, visceral and cerebral approaches to more informed and hopefully more successful professional practice.